052 Risk factors for dominant shoulder injury in elite female Australian cricket players: a prospective study. (3rd March 2020) - Murphy, Myles; Chivers, Paola; Mahony, Kate; Mosler, Andrea
Abstract : Background: In elite Australian cricket, shoulder injuries account for 11% of all injuries and 5.8% of all time-loss injuries in female players. However, even with over 400, 000 females participating in cricket within Australia there are no studies exploring the risk factors for shoulder injury. Objective: Examine the risk factors for dominant shoulder injury in elite female cricketers during the 2017–2018 season. Design: Prospective cohort study. Setting: Australian national cricket league. Participants: A total of 115 elite, female cricketers were included with a mean (SD) age of 26.0(4.4) years. 39 players had missing data for some pre-season risk factors; however, all players were monitored for injury throughout the entirety of the 2017–2018 season. Assessment of risk factors: Univariate and multivariate logistic regression determined the relationship between aerobic fitness and musculoskeletal screening tests with incidence of dominant shoulder injury. Main outcome measurements: Pre-season aerobic fitness, musculoskeletal screening tests (shoulder range of motion, shoulder strength, hip strength, scapula dyskinesis, hypermobility and combined elevation) and dominant shoulder injury requirirng modification of throwing were recorded. Results: Fourteen players developed dominant shoulder injuries however as two resulted from trauma these were excluded so 12 injuries proceeded to analysis. Univariate analysis revealed shoulder internal rotation: external rotation (IR:ER) strength ratio (OR=1.84, p=0.01), back foot hip abduction strength (OR=0.973, p=0.049) and back foot hip adduction: abduction strength ratio (OR=1.44, p=0.047) were significantly associated with injury. Only shoulder IR:ER strength ratio remained significant (p=0.016) in the multivariate logistic regression model with a 79% increased risk of shoulder injury for every 0.1 ratio increase. Conclusions: This study identified that within elite female cricketers, a shoulder IR:ER strength ratio of greater than 1.00 is the strongest risk factor for developing shoulder injury. Therefore, injury risk reduction programs in elite female cricketers which focus on keeping the shoulder IR:ER strength ratio closer to 1:1 may assist to minimise shoulder injury burden.